2018
DOI: 10.1590/1678-7757-2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone repair with strontium- containing nanostructured carbonated hydroxyapatite

Abstract: ObjectiveThis study aimed to evaluate bone repair in rat dental sockets after implanting nanostructured carbonated hydroxyapatite/sodium alginate (CHA) and nanostructured carbonated hydroxyapatite/sodium alginate containing 5% strontium microspheres (SrCHA) as bone substitute materials.MethodsTwenty male Wistar rats were randomly divided into two experimental groups: CHA and SrCHA (n=5/period/group). After one and 6 weeks of extraction of the right maxillary central incisor and biomaterial implantation, 5 μm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
3
29
0
2
Order By: Relevance
“…4,9 Junior et al 10 reported an improvement in the osteoconduction of nHAp in adult rats compared to biological HAp. Carmo et al 11 found similar results to those reported previously when using HAp-based nanocomposites and carbonate structures during osteoconduction and bone repair. However, its fragility and low resistance to mechanical stress have limited its use in orthopedic interventions.…”
Section: Introductionsupporting
confidence: 80%
“…4,9 Junior et al 10 reported an improvement in the osteoconduction of nHAp in adult rats compared to biological HAp. Carmo et al 11 found similar results to those reported previously when using HAp-based nanocomposites and carbonate structures during osteoconduction and bone repair. However, its fragility and low resistance to mechanical stress have limited its use in orthopedic interventions.…”
Section: Introductionsupporting
confidence: 80%
“…The literature points out that strontium (Sr 2+ ) is used in treatments for osteoporosis, bone pain, and bone cancer and can exert double effects of bone stimulation. Studies suggest that the incorporation of Sr 2+ to calcium phosphates seems favorable to bone repair due to its induction properties in bone formation [ 23 , 24 , 46 ]. In a previous study [ 26 ], two concentrations of Sr 2+ were used, 5 wt% and 10 wt%, and it was found that the lower concentration (5%) had higher resistance to compression; however, the ideal dosage of Sr 2+ for incorporation to calcium phosphate is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The number of isomorphic substitutions that hydroxyapatite can undergo incorporating several ions into its structure can optimize its clinical performance, making it more soluble, spatially modifying its crystal structure and favoring its bioabsorption [ 10 ] Previous studies have already carried out the partial replacement of calcium by metals such as zinc [ 10 , 15 , 16 , 17 , 18 , 19 , 20 ] and strontium [ 21 , 22 , 23 , 24 , 25 , 26 ] which are capable of optimizing bone repair.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a nanostructured carbonate hydroxyapatite/calcium alginate (CHA) microsphere was developed by substituting the phosphate group (PO 4 ) with a carbonate group (CO 3 ). The microspheres produced at low temperatures showed lower crystallinity and higher solubility, which favored an earlier resorption time and improved bone regeneration [65,66]. When combined with collagen, nHA/collagen composite scaffolds aimed to mimic the architecture of native bone.…”
Section: Bone Regeneration For Dental Implants and Mandibular Defectsmentioning
confidence: 99%